Helvella cystidiata sp. nov. (Helvellaceae, Ascomycota) from Tibetan Plateau, China - Xu, Rong-Ju; Li, Lu; Zhao, Qi (Phytotaxa, 2022)
During investigations into fungal diversity in the Tibetan Plateau, two Helvella collections were made. Morphological characteristics and phylogenetic analyses of combined ITS and LSU sequence data revealed one collection represents a distinct new species that is introduced as Helvella cystidiata. Helvella cystidiata is characterized by having loosely saddle-shaped pileus, greyish to grey brown hymenium, lacunose stipe and inflated ectal excipulum cells. Furthermore, a known species Helvella lacunosa is reported in Tibetan Plateau. Detailed descriptions, illustrations and a phylogenetic tree to show the placement of two taxa are provided.